PENGARUH MODEL TGT BERBANTUAN APLIKASI WORDWALL TERHADAP HASIL BELAJAR SISWA PADA MATERI SISTEM PERIODIK UNSUR - Dhinda Khansa Meffa; Neti Afrianis (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2026)
This study was motivated by the difficulties many students experience in understanding the subject matter, which in turn affects their learning outcomes. Therefore, an appropriate learning model is needed to help address this issue. The purpose of this study was to determine the effect of implementing the cooperative learning model type TGT (Teams Games Tournament), supported by the Wordwall application, on students' learning outcomes in the topic of the periodic table of elements. The study was conducted in October during the odd semester of the 2025/2026 academic year with Grade X chemistry students at SMA Negeri 4 Pekanbaru. A quasi-experimental method was employed using a pretest-posttest nonequivalent control group design. The sample consisted of 45 students each from the experimental and control classe, selected through cluster random sampling. The research instrument was a mštiple-choice test aligned with indicators of students cognitive abilities. Data were analyzed using a t-test. Results showed a tvalue of 4,834 with a two-tailed significance score of 0,000 and a ttable value of = 1,987. Since the significance value of 0.000< 0.05 and the calculated tvalue exceeded the table value (4,834 > 1,987), the alternative hypothesis (H1) was accepted while the null hypothesis (H0) was rejected. The coefficient of determination yielded an r value of 0.716, indicating that the TGT cooperative learning model assisted by Wordwall influenced students' cognitive abilities regarding the periodic table of elements by 71,6%